Hubungan antara Father Involvement dengan Regulasi Emosi pada Remaja Madya di Kota Padang - Juliyanti, Annisa; Magistarina, Elrisfa (AHKAM, 2024)
This study aims to describe the relationship between father involvement and emotion regulation in middle adolescents in Padang City. The research design used in this study is to use quantitative research and regression research design. This study was conducted on 348 adolescents with the sampling technique used was purposive sampling technique. Data were collected using Finley & Schwartz's Father Involvement Scale and Gross's Emotion Regulation Questionnaire which have been adapted to Indonesian. Hypothesis testing using product moment correlation showed a positive and significant relationship between father involvement and emotion regulation in middle adolescents with a correlation coefficient of 0.267 and a significance value of 0.000. Based on the results of research and hypothesis testing that has been carried out regarding the relationship between father involvement and emotional regulation in middle adolescents in Padang City, it can be concluded that. There is a positive relationship between father involvement and emotional regulation in middle adolescents in Padang City, meaning that the higher the father involvement that adolescents have, the higher the level of regulation ability that adolescents have.